2014
DOI: 10.4049/jimmunol.1303180
|View full text |Cite
|
Sign up to set email alerts
|

A Polysaccharide Virulence Factor of a Human Fungal Pathogen Induces Neutrophil Apoptosis via NK Cells

Abstract: Aspergillus fumigatus is an opportunistic human fungal pathogen that sheds galactosaminogalactan (GG) into the environment. Polymorphonuclear neutrophils (PMNs) and NK cells are both part of the first line of defense against pathogens. We recently reported that GG induces PMN apoptosis. In this study, we show that PMN apoptosis occurs via a new NK cell–dependent mechanism. Reactive oxygen species, induced by the presence of GG, play an indispensable role in this apoptotic effect by increasing MHC class I chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 65 publications
4
49
0
Order By: Relevance
“…For instance, Cryptococcus elaborates a dense polysaccharide capsule, which shields cell wall carbohydrates from detection by the immune system (15,16). As cell wall carbohydrates are the primary PAMPs in fungal pathogens, we focused our analysis on carbohydrates that are known or suspected to provoke an immune response in other fungal species, including mannan (17)(18)(19)(20), ␤-1,3-glucan (21-30), galactosaminogalactan (GAG) (31)(32)(33)(34)(35)(36), and chitin (37)(38)(39)(40)(41)(42)(43)(44)(45). Freshly harvested Exserohilum rostratum spores were grown in complete RPMI at 37°C with 5% CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Cryptococcus elaborates a dense polysaccharide capsule, which shields cell wall carbohydrates from detection by the immune system (15,16). As cell wall carbohydrates are the primary PAMPs in fungal pathogens, we focused our analysis on carbohydrates that are known or suspected to provoke an immune response in other fungal species, including mannan (17)(18)(19)(20), ␤-1,3-glucan (21-30), galactosaminogalactan (GAG) (31)(32)(33)(34)(35)(36), and chitin (37)(38)(39)(40)(41)(42)(43)(44)(45). Freshly harvested Exserohilum rostratum spores were grown in complete RPMI at 37°C with 5% CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Second, GAG appeared to reduce neutrophil infiltrates in the lung during infection. GAG induced neutrophil apoptosis [17]. It was shown that polymorphonuclear leukocyte (PMN) apoptosis occur via a NK cell-dependent mechanism.…”
Section: Gag Is a Virulence Factor In A Fumigatusmentioning
confidence: 99%
“…Remarkably, this mutant has been described as hyperadhesive to epithelial cells [18], and this hyperadhesive phenotype was further shown to be related to GAG. In addition, due to its immunomodulatory properties, GAG has also been described as an important virulence factor [20,21,22].…”
Section: Accepted Manuscriptmentioning
confidence: 99%